Rheological investigation on the effect of shear and time dependent behavior of waxy crude oil - Japper-Jaafar, A. (EDP Sciences, 2014)
Rheological measurements are essential in transporting crude oil, especially for waxy crude oil. Several rheological measurements have been conducted to determine various rheological properties of waxy crude oil including the viscosity, yield strength, wax appearance temperature (WAT), wax disappearance temperature (WDT), storage modulus and loss modulus, amongst others, by using controlled stress rheometers. However, a procedure to determine the correct parameters for rheological measurements is still unavailable in the literature. The paper aims to investigate the effect of shear and time dependent behaviours of waxy crude oil during rheological measurements. It is expected that the preliminary work could lead toward a proper rheological measurement guideline for reliable rheological measurement of waxy crude oil. Â© 2014 Owned by the authors, published by EDP Sciences.